Identificação do consumidor-marca : uma investigação do caminho simbólico-instrumental no contexto dos influenciadores de mídias sociais - Faria, Ana Flávia de (2022)
The popularity of social media influencers has been a focus for companies to promote products and with the success among their followers, influencers have started to develop their own brands and product lines. It is known that consumers use brands to satisfy their instrumental needs, focusing on the functional benefits of products; and symbolic needs, using brands to express aspects of their identities. In this way, it becomes relevant to understand by which routes consumers consume these brands and, if there is a difference in future behaviors in relation to other brands. In this context, the present study aims to analyze the moderating effect of influencer brands (versus non-influencers) on the symbolic-instrumental structure of consumption and its influence on the generation of function and extra-function behaviors. To meet this objective, a survey was conducted with 194 consumers. Data were analyzed using a set of techniques associated with Structural Equation Modeling (SEM) with the PLS-SEM approach. The results indicated that in the symbolic consumption route, the consumer's identification with the brand is the result of congruence with the brand and is responsible for ewom behavior. On the other hand, repurchase intention is explained by the instrumental consumption route, driven by quality perceived and partially mediated by brand trust. The results also showed that for influencer brands there is a partial mediation effect by brand trust, with quality perceived being significantly responsible for the generation of repurchase intention and word-of-mouth behaviors. The same cannot be observed for the other brands. The study contributes to a better understanding of the symbolic and instrumental paths in the relationship of consumers with the different types of brands, and in the generation of future behaviors.